PROTECTION AND REMEDY FOR CULTURAL HERITAGE BUILDINGS IN CHINESE TOURISM CITIES, WITH AUTHENTICITY AND MINIMAL INTERVENTION: A CASE STUDY OF ZHEJIANG AREA, CHINA - JIANREN, SHI (ITB Journal Publisher, LPPM ITB, 2011)
Human civilization and non-renewability in the historic buildings determine the great value and the importance of protection. How to protect and remedy the historic buildings is the key of protecting the urban cultural context, especially keep the specific historic features. There are two principles of minimal intervention and maximum authenticity of their historical information. Based on the practice of the Qing-an and An-lan Hall Projection, the technologies and methods of protecting the historic buildings were discussed, including two aspects: carpentry engineering and masonry engineering. These measurements constitute to similar projects in the southeastern region of China.